Legal knowledge and its relationship to selective attention using the Rehcom system for Al-Rafidain basketball athletes - Hayder Naji Habash Al-Shawi1 , Shaimaa Farhan Mohammed Al-Jubouri2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
the research objectives were to identify the reality of legal knowledge and selective attention using theRehcom system for Al-Rafidain basketball players, and to identify the correlation between selectiveattention and the legal knowledge of Al-Rafidain basketball players , And prediction of legal knowledgein terms of selective attention of players Al-Rafidain Basketball Club, the researcher used the descriptiveapproach in the survey method and the correlational relations on the 19 Al-Rafidain Basketball Club players.Conclusions In light of the research results and the statistical analysis of the data obtained, the researcherreached the following conclusions, that there is a relationship between legal knowledge and The selectiveattention of basketball players, the variable and the selective attention, and through the test preparation in theRehcom system, has a very clear relationship to improving and developing a variable and selective attention.